Los rincones de juego trabajo para el desarrollo de la comunicación oral de la niñas y niños II de 4 a 5 años de la escuela de educación basica Carlos Augusto Ortega Erique del cantón Catamayo provincia de Loja. Periodo 2014-2015 - Pullaguari Cango, Liliana Marisol (2016)
This research includes a study on: The corners of play work for the development of oral communication of children the initial II 4 to 5 years of the School of Basic Education Carlos Augusto Ortega Erique Canton Catamayo Loja Province. 2014-2015. It began with a general objective, contribute to the development of oral communication through play corners work. In order to give importance to the corners for the development of oral communication to improve this problem. The methodology used in this research work consists of the following methods: scientific, analytical and synthetic, hermeneutical and statistical method. To this was applied as direct observation technique which allowed me to observe and verify that not make use of the corners on the grounds of lack of materials in every nook and for that reason may not develop oral communication. Through interviews applied to teaching was used, which provided information on the corners of play work and relationship with oral communication, and finally the observation guide this same group was applied to diagnose the level of communication through oral play corners work. workshop activities was also applied in the different corners of play work for children who have a low percentage in the development of oral communication. In the study sample it is counted a population of 16 children. The result of the interview with the teacher was found to have a knowledge of oral communication of girls. It can be concluded that play corners work are feasible for the development of oral communication.